DFT Calculation on 76 Polychlorophenazines: Their Thermodynamic Function and Implication of Cl Substituted Position - Hong-Xia Yu; Hui Liu; Zun-Yao Wang; Lian-Sheng Wang (International Journal of Chemical Engineering)
Thermodynamic functions, including enthalpy (Hθ) and entropy (Sθ) for 76 polychlorophenazines (PCPZs) in the gas state at 298.15 K and 101.325 kPa, have been calculated using the B3LYP/6-31G∗ level with Gaussian 03 program, and considered on solvation affects. Total free energy in water (Gw) was calculated with the same program. Based on these data, the isodesmic reactions were designed to calculate the standard formation heat (ΔfHθ) and standard free energy of formation in water (ΔfGwθ). The dependences of these thermodynamic parameters on the numbers and positions of chlorine substitution (NPCS) were discussed. It is suggested that Sθ,  ΔfHθ, and ΔfGwθ of PCPZs varied greatly with NPCS. Moreover, the values of molar heat capacity at constant pressure (Cp,m) from 200 to 1800 K for PCPZ congeners were calculated using a statistical thermodynamics calculation program based on Gaussian output files, and the temperature-dependence relation of Cp,m was obtained using the least-squares method. In addition, according to the relative magnitude of their ΔfGwθ, the relative stability order of PCPZ congeners was theoretically proposed.